Feasibility and image quality of myocardial perfusion imaging by CMR in patients with conditional and non-conditional cardiac devices. (3rd October 2022) - Meier, C; Bietenbeck, M; Drakos, S; Chamling, B; Vehof, V; Stalling, P; Yilmaz, A
Abstract: Purpose: First, to determine image quality using different cardiovascular magnetic resonance (CMR) perfusion protocols in patients with all available active device types in a real-world setting, including non-conditional devices. Second, to demonstrate feasibility of high-quality perfusion imaging using spoiled gradient echo (sGE) protocols for non-invasive stress-testing. Methods: From August 2020 to March 2022, N=222 patients with active cardiac implantable electronic devices (CIED) were scanned on a 1.5-T MR scanner (Philips Ingenia and Ambition). Our CMR scanning protocol was tailored to the clinical indication, and whenever myocardial perfusion imaging was possible, both a conventional steady-state-free-precession (SSFP)-based and a modified sGE-perfusion protocol were applied. Such a tailored perfusion protocol was performed in N=119 patients (70% men) with exclusively left-sided devices (pacemaker (PM), n=45; implantable cardioverter-defibrillator (ICD), n=46; subcutaneous ICD (S-ICD), n=15 and cardiac resynchronization therapy-pacemaker (CRT-P, n=5) or -defibrillator (CRT-D, n=8) with a percentage of 10% non-conditional devices. For assessment of image quality, a semi-quantitative 4-point grading scale was used based on a standard 16-segment model. Results: A total of N=33 stress-tests with either regadenosone, adenosine or dobutamine and N=86 rest perfusion protocols were performed. Asynchronous pacing was required in 34% of the patients due to a heart rate of <40bpm. Device interrogation before and after CMR scanning showed no significant changes. Image quality was substantially better in sGE-based perfusion protocols compared to conventional SSFP-based perfusion in ICD, CRT-D and S-ICD patients (p<0.001). In patients with PM/ CRT-P image quality was neither significantly impaired in SSFP- nor in sGE-based protocols. Most device artefacts were located primarily in the anterior myocardial segments (1, 7, 13) in transvenous implanted devices and lateral in SICD-patients. A significant relationship between the extent of device artefacts and the parameters LVEDV (p=0.03), LVESV (p=0.005) and non-conditional devices (p=0.029) in SSFP-perfusion protocols were found in patients with PM/CRT-P. In contrast, there was no correlation between clinical and CMR-parameters in patients with ICD/ CRT-D. In S-ICD-patients, there was an inverse relationship between the extent of device artefact and age (p=0.006), BMI (p=0.001) in sGE-perfusion. Conclusion: Myocardial perfusion imaging by CMR is safe and feasible with high image-quality in patients with all kinds of CIEDs – including MR-conditional as well as non-conditional devices. When performing CMR-based myocardial perfusion imaging in patients with left-sided ICD/CRT-D/S-ICD, a sGE-based perfusion-protocol should be preferred compared to conventional SSFP-based perfusion protocols in order to achieve artefact-free and well interpretable images. Funding Acknowledgement: Type of funding sources: None.